Chapter 11 Moral Neuroenhancement - Douglas, Thomas (Taylor & Francis, 2018)
In recent years, philosophers, neuroethicists, and others have become preoccupied with "moral enhancement." Very roughly, this refers to the deliberate moral improvement of an individual's character, motives, or behavior. In one sense, such enhancement could be seen as "nothing new at all" (Wiseman, 2016, 4) or as something philosophically mundane: as G. Owen Schaefer (2015) has stated, "Moral enhancement is an ostensibly laudable project. . . .